Prostate-specific antigen glycoprofiling as diagnostic and prognostic biomarker of prostate cancer. Issue 2 (15th February 2019) - Tkac, Jan; Gajdosova, Veronika; Hroncekova, Stefania; Bertok, Tomas; Hires, Michal; Jane, Eduard; Lorencova, Lenka; Kasak, Peter
Abstract : The initial part of this review details the controversy behind the use of a serological level of prostate-specific antigen (PSA) for the diagnostics of prostate cancer (PCa). Novel biomarkers are in demand for PCa diagnostics, outperforming traditional PSA tests. The review provides a detailed and comprehensive summary that PSA glycoprofiling can effectively solve this problem, thereby considerably reducing the number of unnecessary biopsies. In addition, PSA glycoprofiling can serve as a prognostic PCa biomarker to identify PCa patients with an aggressive form of PCa, avoiding unnecessary further treatments which are significantly life altering (incontinence or impotence).